(untitled) (Revista do Tribunal Regional Federal da 3ª Região, 2011)
From this issue onwards, in order to make it easier to study and research the subjects covered, the judgments and monocratic decisions will be grouped according to the predominant subject of the judgment. In an effort to make the magazine more dynamic, we have once again opened up space for the publication of doctrinal articles by the magistrates of the Federal Court of the 3rd Region, to whom I offer my sincere thanks for the collaboration that so enriches our magazine with works that deal with current and important issues. In this way, we hope to contribute, within the limits of our honorable regimental attributions, to the dissemination of our jurisprudence, the fruit of the exercise of our jurisdictional mission.